2013
DOI: 10.1371/journal.pone.0081774
|View full text |Cite
|
Sign up to set email alerts
|

IL-4/IL-13-Dependent and Independent Expression of miR-124 and Its Contribution to M2 Phenotype of Monocytic Cells in Normal Conditions and during Allergic Inflammation

Abstract: Monocytic cells exhibit a high level of heterogeneity and have two distinct modes of their activation: 1) classical M1 path associated with inflammation and tissue damage, and 2) alternative M2 path. Although it has been demonstrated that M2 macrophages play an important role in the regulation of the allergic immune responses, tissue maintenance and repair, little is known about the mechanisms that determine the M2 phenotype. We have previously shown that miR-124 is expressed in microglia that exhibit the M2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 45 publications
5
134
0
1
Order By: Relevance
“…asthmatic donors express marker genes of M2 polarization more highly than monocytes from healthy individuals (94,95). Therefore, dysregulation of these negative regulators of Th2 cytokine signaling represents another mechanism of pathogenesis that contributes to allergic inflammation.…”
Section: Socs1 Regulates Il-4-induced Irs-2 Signaling In Human Monocytesmentioning
confidence: 99%
“…asthmatic donors express marker genes of M2 polarization more highly than monocytes from healthy individuals (94,95). Therefore, dysregulation of these negative regulators of Th2 cytokine signaling represents another mechanism of pathogenesis that contributes to allergic inflammation.…”
Section: Socs1 Regulates Il-4-induced Irs-2 Signaling In Human Monocytesmentioning
confidence: 99%
“…[61][62][63][64][65][66] In THP-1, the expression of miR-125b is upregulated in macrophages, either after PMA-induced differentiation or M1 polarizing conditions, as well as in monocytes after LPS stimulation. Several reports showed that miR-125b is enriched in macrophages and is an LPS-regulated miRNA.…”
mentioning
confidence: 99%
“…In addition, miRNAs have been reported to regulate macrophage polarization. Among various miRNAs, miR-124 has been reported to polarize macrophages toward the M2 phenotype (85). Overexpression of miR-124 in macrophages decreased expression of MHC class II and CD86 (M1 markers) and upregulation of Fizz1 and Arg1 (M2 markers).…”
Section: M1-to-m2 Repolarization As An Anti-inflammatory Therapeutic mentioning
confidence: 99%
“…However, expression of miR-124 in microglia does not depend on IL-4 and/or IL-13 pathway, whereas miR-124 expression in lung macrophages was IL-4 and IL-13-dependent. Upregulation of several M2 markers and downregulation of the M1 markers in M2-polarized macrophages was absent by transfecting the macrophages with a miR-124 inhibitor (85,86). miR-223 is another miRNA that regulates M2 macrophage activation (87).…”
Section: M1-to-m2 Repolarization As An Anti-inflammatory Therapeutic mentioning
confidence: 99%